MICROBIAL DIVERSITY OF COASTAL WATERS OF ODESA BAY OF THE BLACK SEA - Н. Ю. Васильєва; К. Д. Крилова; Й. Б. Кристофферсен; О. А. Дубровіна; В. О. Іваниця (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2018)
The aim of the study was to determine the biodiversity of the prokaryotic microbiota of the coastal water of Odesa Bay of the Black Sea with the help of metagenomics analysis. Methods. Sample of sea water was taken in the area of Нydrobiological station of Odesa I. I. Mechnikov National University (46°26'28.2"N 30°46'20.0" E). Sample of sea water was taken from the horizon of 100 cm and filtered through 0.22 μm membrane filters (Sartorius). Total DNA was isolated from the collected microorganisms using the PowerWater DNA isolation kit (catalog no.14900-50- NF) according to the manufacturer's instructions (MO BioLaboratories). Total DNA extraction has been performed according to the manufacturer's instructions (MO BioLaboratories) from collected microorganisms using the PowerWater DNA isolation kit (catalog no.14900-50-NF). To determine the microbial diversity with the help of metagenomic analysis, there were carried out targeted sequencing performed on the Illumina MiSeq platform after amplify v4 region of the 16S rRNA gene. The obtained sequences in the fastq format were analyzed in the miniconda3 shell with used next programs: Fastqcv.0.11.2., Trimmomatic, Cutadapter, SPAdes, Centrifuge and Krona. Results. As a result of the metagenomics 16S rRNA gene analysis of the coastal waters of Odesa Bay about 261 197 annotated sequences were defined. The representatives of main departments of the domain Bacteria were identified: Proteobacteria, Bacteroidetes, Firmicutes, Actinobacteria, Cyanobacteria, Tenericutes, Spirochaetia, Fusobacteria, Thermotogae, Deinococci, Aquificae , Chlorobia, Chloroflexi ,Verrucomicrobia, Deferribacteres, Planctomycetes, Chlamydiia, Acidobacteria, Nitrospirae, Ignavibacteriae, Thermodesulfobacteria, Dictyoglomia, Elusimicrobia, Synergistia, Fibrobacteria, Gemmatimonadetes. The most common departments of Bacteria domain were Proteobacteria (68.0%) and Bacteroidetes (19.0%). The representatives of Gammaproteobacteria (63.0%) and Alphaproteobacteria (31.0%) were dominated among the Proteobacteria. The presence of small amount of representatives of the Archaea domain (less than 0.5%) as the classes Euryarchaeota, Thaumarchaeota, Crenarchaeota was shown. Conclusion. A comparative analysis of the presented results and those that were obtained during previous studies of the biological diversity of microbial communities in the Black Sea estuaries and in the region of the Zmiiniy Island made it possible to determine the main differences in their composition. As it was shown, microbial communities of the coastal water of Odesa Bay, water of the Khadzhybei estuary and in the region of the Zmiiniy Island is manifold and is represented mainly by the members of Proteobacteria and Bacteroidetes while representatives from Cyanobacteria phylum is dominate in the Dry and Dniester estuaries.